Visible Enhanced Photodetector Made by Spray Pyrolysis - Ismail, Raid A.; A. Sultan, Omar A. (Iraqi Journal of Laser, 2002)
Barium–doped TiO2 / n-Si photodetector was fabricated by spray pyrolysis exhibited visible enhancement responsivity profile with peak response at 600 nm flat response between 650 and 900 nm. The quantum efficiency was 30% and specific detectivity was 5x1012 W-1Hz1/2cm at peak response. The GaAlAs laser diode was used to estimate the rise time of the detector.